In situ real-time measurement of physical characteristics of airborne bacterial particles - Jung, Jae Hee; Lee, Jung Eun (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Bioaerosols, including aerosolized bacteria, viruses, and fungi, are associated with public health and environmental problems. One promising control method to reduce the harmful effects of bioaerosols is thermal inactivation via a continuous-flow high-temperature short-time (HTST) system. However, variations in bioaerosol physical characteristics - for example, the particle size and shape - during the continuous-flow inactivation process can change the transport properties in the air, which can affect particle deposition in the human respiratory system or the filtration efficiency of ventilation systems. Real-time particle monitoring techniques are a desirable alternative to the time-consuming process of microscopic analysis that is conventionally used in sampling and particle characterization. Here, we report in situ real-time optical scattering measurements of the physical characteristics of airborne bacteria particles following an HTST process in a continuous-flow system. Our results demonstrate that the aerodynamic diameter of bacterial aerosols decreases when exposed to a high-temperature environment, and that the shape of the bacterial cells is significantly altered. These variations in physical characteristics using optical scattering measurements were found to be in agreement with the results of scanning electron microscopy analysis. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: BACILLUS-SUBTILIS SPORES; ULTRAVIOLET GERMICIDAL IRRADIATION; ESCHERICHIA-COLI; PERFORMANCE EVALUATION; THERMAL INACTIVATION; AIR-FLOW; BIOAEROSOLS; EXPOSURE; MICROORGANISMS; NANOPARTICLES